Obraz samego siebie a zachowania zdrowotne młodzieży studiującej = The self-concept and health behaviour in studing youth - Kowalski, Paweł (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to diagnose the self-concept and health behavior in studying youth and to assess the interdependence between the self-concept and health behavior in the resear-ched. 214 students were involved in the study. A diagnostic survey was used as the study method; the technique employed was a questionnaire; and W.H. Fitts` Self-Concept Scale and a questionnaire on health behavior were used as research tools.`
Keywords: obraz samego siebie; zachowania zdrowotne; młodzież studiująca; uwarunkowania zdrowia; self-concept; health behavior; studying youth; determinants of health